Bolshevik Food Policy in Kuban and Black Sea Region: Examining Conflict between RCP(b) and Rural Population in Early 1920s - Yu. A. Yakhutl; M. S. Dirivyankina (Научный диалог, 2025)
This study explores the content of the Bolshevik food policy in Kuban and the Black Sea region during the transitional period from War Communism to the New Economic Policy in the early 1920s. Employing historical-genetic, retrospective methods, and a communicative approach, the article draws on various written sources, including materials from party and Soviet authorities. It is noted that the shift to new methods of food procurement and the establishment of new land relations in the Cossack region took on a protracted character. The active implementation of military-communist leadership methods by the Bolsheviks contributed to an increase in resistance from the rural population. The authors argue that the armed opposition of the rural populace to tax policies intensified repressive measures from the RCP(b) (Russian Communist Party (Bolsheviks)). The absence of political consensus in the region, characterized by a predominance of commodity-based agriculture, necessitated the search for a compromise. It is revealed that such a compromise was achieved through the military dominance of Soviet power. The study establishes that, at this stage of interaction between the Bolsheviks and the rural population, the land issue was not of primary importance and was secondary to the food question. The authors conclude that by 1924, when the military conflict had finally been resolved, another attempt was made to establish dialogue between the authorities and the rural population, taking into account their economic interests.